2010
DOI: 10.1103/physrevlett.105.155501
|View full text |Cite
|
Sign up to set email alerts
|

Metallic Liquids and Glasses: Atomic Order and Global Packing

Abstract: In this Letter, we have revealed the common structural behavior of metallic glasses through scrutinizing the evolution of pair distribution functions from metallic liquids to glasses and statistically analyzing pair distribution functions of 64 metallic glasses. It is found that the complex atomic configuration in metallic glasses can be interpreted globally as a combination of the spherical-periodic order and local translational symmetry. The implications of our study suggest that the glass transition could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
79
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(99 citation statements)
references
References 29 publications
(51 reference statements)
14
79
1
Order By: Relevance
“…It can be seen that at least five pronounced peaks are present in the range of about 1.2 nm, which indicates that there exists a structural order from short to medium range in glasses. We analysed the scaled peak positions R i /R 1 (i ¼ 1,2,3,4,5) in PCFs by fitting each peak with a Gaussian function 9 It has been demonstrated that the constants associated with the values of R i /R 1 (i ¼ 2,3,4,5) in glassy Ni correspond to some relative atomic positions in fcc lattice structure 9 , so that we naturally examine the relative atomic positions of R 0 i =R 0 1 (i ¼ 1-14) for fcc and bcc lattice structures, respectively, and the data are summarized in Table 2. Here, R 0 i (i ¼ 1-14) denotes the distance of the ith nearest neighbour atoms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be seen that at least five pronounced peaks are present in the range of about 1.2 nm, which indicates that there exists a structural order from short to medium range in glasses. We analysed the scaled peak positions R i /R 1 (i ¼ 1,2,3,4,5) in PCFs by fitting each peak with a Gaussian function 9 It has been demonstrated that the constants associated with the values of R i /R 1 (i ¼ 2,3,4,5) in glassy Ni correspond to some relative atomic positions in fcc lattice structure 9 , so that we naturally examine the relative atomic positions of R 0 i =R 0 1 (i ¼ 1-14) for fcc and bcc lattice structures, respectively, and the data are summarized in Table 2. Here, R 0 i (i ¼ 1-14) denotes the distance of the ith nearest neighbour atoms.…”
Section: Resultsmentioning
confidence: 99%
“…Although significant progress has been made and provided insights into the atomic-level structure and short-to-mediumrange order in glasses [3][4][5][6][7][8][9][10][11][12][13][14] , the way of leading to the mediumrange order is still unclear [5][6][7][8][9][10] . Does a universal rule exist that nature follows to construct a glass structure as what has been discovered for crystals?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work on the structure of metallic glasses represents the MRO in the metallic glass as a combination of spherical periodic order and translational symmetry. 24 They achieved the global structural information by calculating the position ratios between the peaks related to the MRO and the first peak in RDF curves, and found that the ratio values are well consistent with the atomic arrangement in fcc crystals along the dense-packing direction. This is a simple and reasonable method to study the local order structure of liquids or metallic glasses from a global viewpoint.…”
Section: Liquid Structure and Glass Transitionmentioning
confidence: 91%
“…24 They represented the MRO structure as a combination of spherical periodic order and local translational symmetry. The atomic arrangement within the MRO prefers the dense-packed positions in fcc or hexagonal close packing (hcp) lattices.…”
mentioning
confidence: 99%